Apatinib Plus Camrelizumab With/Without Chemoembolization for Hepatocellular Carcinoma: A Real-World Experience of a Single Center - Ju, Shuguang; Zhou, Chen; Yang, Chongtu; Wang, Chaoyang; Liu, Jiacheng; Wang, Yingliang; Huang, Songjiang; Li, Tongqiang; Chen, Yang; Bai, Yaowei; Yao, Wei; Xiong, Bin (Frontiers in Oncology, 2022)
Objective To compare the efficacy and safety of transarterial chemoembolization (TACE) plus apatinib plus camrelizumab (TACE+AC) and apatinib plus camrelizumab (AC) in the treatment of unresectable hepatocellular carcinoma (HCC) in a real-world setting. Methods In this single-center retrospective study, the data of patients with unresectable HCC who had received TACE+AC or AC treatment during March 2017 to May 2021 were assessed. Patients in the AC group received intravenous administration of camrelizumab 200mg every 3 weeks and oral apatinib 250 mg/day treatment. Patients in the TACE+AC group received the same dose of camrelizumab and apatinib 1weeks after TACE. The primary endpoint of the study was overall survival (OS), objective response rate (ORR), disease control rate (DCR), adverse events (AEs) as the secondary endpoints. Results A total of 108 patients were enrolled in the study. There were 52 patients in the AC group and 56 patients in TACE+AC group. Median OS was significantly longer in the TACE+AC group than in the AC group (24.8 vs 13.1 months; P=0.005). Patients in the TACE+AC group achieved a higher ORR (24 [42.9%] vs 9 [17.3%], P=0.004) than those in the AC group. Patients in the TACE+AC group also achieved a higher disease control rate (DCR) (48 [85.7%] vs 30 [57.7%], P=0.001) than patients in the AC group. There was no significant difference in the incidence of AEs related to apatinib and camrelizumab between the two groups, except for gastrointestinal reaction (P>0.05, all; P<0.05, gastrointestinal reaction). Conclusion TACE plus apatinib plus camrelizumab significantly improved OS, ORR and DCR over apatinib plus camrelizumab in patients with unresectable HCC. AEs were tolerable and manageable.